SOLUSI NUMERIK UNTUK PERSAMAAN NAVIER-STOKES DIMENSI DUA DENGAN METODE BEDA HINGGA - , VINALIA EKA WARDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A moving fluid such as liquid can be made into a form of mathematical modeling of the Navier-Stokes equations. Navier-Stokes equations are second order nonlinear partial differential equation that can be solved using finite difference method . Solving the partial differential equations using finite difference method produces systems of linear equations that must be solved by Successive Over Relaxation (SOR) iteration. Furthermore the two-dimensional simulation of incompressible fluid flow can be acquired from that methods by including the effect which depends on the time.